2019
DOI: 10.1007/s10231-019-00853-w
|View full text |Cite
|
Sign up to set email alerts
|

Regular subgroups with large intersection

Abstract: In this paper we study the relationships between the elementary abelian regular subgroups and the Sylow 2-subgroups of their normalisers in the symmetric group Sym(F n 2 ), in view of the interest that they have recently raised for their applications in symmetric cryptography.2010 Mathematics Subject Classification. 20B35, 20D20, 94A60.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…From now on the chief series F will be fixed, and so, without ambiguity, we will write Σ n and U n to denote respectively Σ F and U F . In [4] it is proved that U n contains, as normal subgroups, exactly two conjugates of T , namely T and T U n = T g , for some g ∈ Sym(2 n ). It is also shown that the normalizer N 1 n = N Sym(2 n ) (U n ) interchanges by conjugation these two subgroups and that N 1 n contains U n as a subgroup of index 2.…”
Section: Elementary Abelian Regular 2-groups and Their Chain Of Normamentioning
confidence: 99%
See 1 more Smart Citation
“…From now on the chief series F will be fixed, and so, without ambiguity, we will write Σ n and U n to denote respectively Σ F and U F . In [4] it is proved that U n contains, as normal subgroups, exactly two conjugates of T , namely T and T U n = T g , for some g ∈ Sym(2 n ). It is also shown that the normalizer N 1 n = N Sym(2 n ) (U n ) interchanges by conjugation these two subgroups and that N 1 n contains U n as a subgroup of index 2.…”
Section: Elementary Abelian Regular 2-groups and Their Chain Of Normamentioning
confidence: 99%
“…. representing the partial sums of the famous sequence {b j } of the number of partitions of the integer j into at least two distinct parts, already studied by Euler [15], and a sequence of group-theoretical invariants. Our sequence arises in connection with a problem in algebraic cryptography, namely the study of the conjugacy classes of affine elementary abelian regular subgroups of the symmetric group on 2 n letters [4,9,10]. This is relevant in the cryptanalysis of block ciphers, since it may trigger a variation of the well-known differential attack [7]: a statistical attack which allows us to recover information on the secret unknown key by detecting a bias in the distribution of the differences on a given set of ciphertexts when the corresponding plaintext difference is known.…”
Section: Introductionmentioning
confidence: 99%
“…U n ] is necessarily contained in the unique subgroup of index 4 in T g n and normal in U n , which is T g n ∩ T n (see [ACGS19]). Hence (T n • T g n )/T n lies in the second term of the upper central series of the quotient…”
Section: Theoretical Evidencementioning
confidence: 99%
“…In a recent paper [ACGS19], we considered the elements of the conjugacy class T Sym(2 n ) which are subgroups of the affine group AGL(T ). We showed that, if T g ∩ T has index 4 in T , then there exists a Sylow 2-subgroup U < AGL(T ) containing both T g and T as normal subgroups.…”
Section: Introductionmentioning
confidence: 99%
“…Integer partitions into distinct parts may appear in several areas of mathematics, sometimes unexpectedly. For example, they have been recently shown to be linked to the set of generators of groups in a group-theoretical problem related to cryptography [ACGS19,ACGS21a]. In particular, Aragona et al showed that the generators of a given group are linked to partitions into distinct parts which satisfy a condition of non-refinability [ACGS21b] together with a condition on the minimal excludant.…”
Section: Introductionmentioning
confidence: 99%